AN ANALYSIS OF SARCASM IN TIK TOK @RIANFAHARDHI - Yanti, Amelda; Yusmalinda, Yusmalinda (STBA Prayoga Padang, 2023)
Abstract The purpose of this article is to analyze the types of sarcasm in TikTok @rianfarhadhi. Sarcasm is a type of figure of speech that uses scathing words to hurt other people's feelings and can be in the form of ridicule. This research was qualitative research. The data were taken from TikTok @rianfarhadhi account. The data were analyzed based on Camp’s types of sarcasm (2011). The writer found 27 data that were categorized into four types of sarcasm used in the TikTok account. The result of this study revealed that there were 7 proporsitional sarcasm, 5 lexical sarcasm, 6 like-prefix sarcasm, and 9 illocutionary sarcasm. In conclusion, the writer found the four types of sarcam proposed by Champ (2011) in @rianfarhadi account.